Evaluation System of Tax Exemptions and Its Impact on Local Investments: An Applied Study at the Iraqi General Tax Authority for the Period 2015–2024 - Ayyed Jasim Abbood (Research Parks Publishers, 2026)
It aims this Search to evaluation system Exemptions tax in Iraq and study Its impact on Investments Local during period From 2015 to 2024, from during study Applied in Authority public For taxes Iraqi. Depends Search on Curriculum Applied Descriptive Analytical, user Data Official For the Authority and reports ministry Planning and the bank Central Iraqi, In addition to Interviews with number from Officials Taxes and investors Locals. It was done. analysis relationship between Exemptions tax and indicators Investment Local, like number Projects New and value investment per sector economic, Using Methods Statistics The occasion and models decline Linear. It showed Results that Exemptions tax He was she has effect positive marked on incentivize some Sectors Investment, especially Industrial And agricultural while Stayed Its impact limited in sectors Other because of Factors bureaucracy And legislative. He concludes Search to that to improve efficiency system Exemptions tax And directing it about Sectors The most productivity and attraction For investment It can enhance from Her role Its importance as a tool Effective and efficient To stimulate Development Economic. As well. He presents Search Recommendations practical To develop Policies tax In what Contributes in to improve environment Investment Local in Iraq.